Upaya Guru Pendidikan Agama Islam (PAI) dalam Menanamkan Nilai Menghormati Keyakinan Orang Lain di SMP N 2 Ampek Nagari - Putri, Melia Pratama; Rahman, Rini (ALSYS, 2023)
Seeing that in this school students have different beliefs, it is very important for teachers to instill the value of tolerance, one of which is respecting other people's beliefs because there are many phenomena that occur related to relations between religious communities which cause divisions. This research aims to see the efforts of Islamic Religious Education teachers in instilling the value of respecting other people's beliefs at SMP N 2 Ampek Nagari, Agam Regency. This research uses a qualitative method with a descriptive approach. Sources were taken from school principals, PAI teachers, and students both Muslim and non-Muslim. To obtain data, researchers used observation guidelines and interview guidelines as well as documentation as research instruments. The analysis technique used is the Milles and Huberman analysis technique using data analysis, data reduction, data presentation and conclusions. The results of the research show that there are several efforts made by PAI teachers to instill the value of respecting other people's beliefs at SMP N 2 Ampek Nagari, Agam Regency, in the form of providing routine advice before PAI lessons, giving punishment and sanctions to students who commit deviant acts that are not in accordance with the rules. there are mainly related to beliefs such as excommunicating, denouncing other people's religions and other acts of violence, making a PAI study contract which contains several rules that must be fulfilled by students while studying PAI, and getting used to not disturbing each other's beliefs when praying.